The remediation of agricultural land contaminated by heavy metals - Radočaj, Dorijan (Array, 2020)
The presence of heavy metals in an agricultural land is the primary cause of food product toxicity of a herbal and animal origin associated with a contaminated agricultural land. The anthropogenic sources of pollution, especially the fertilizers and pesticides in agriculture, are the primary sources of agricultural land contamination with heavy metals. The heavy metals whose monitoring is prescribed by the current legislation of the Republic of Croatia include cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), nickel (Ni), lead (Pb) and zinc (Zn). The aim of this paper is to provide a review of heavy metals that cause contamination of an agricultural land, as well as a review of remediation technologies applied to reduce contamination. Furthermore, the paper considers three groups of remediation technologies, i.e., the biological, chemical, and physical ones, analyzing the applicability, efficiency, cost-effectiveness and accessibility in Croatia to encourage their wider implementation. The biological remediation technologies, also known as phytoremediation, met the set criteria the most, which currently renders them most applicable to the mildly‐ and moderately‐contaminated agricultural land. The chemical and physical remediation technologies are generally more suitable for the remediation of a severely contaminated agricultural land, applied individually or in combination with the phytoremediation methods due to the high cost.